ANALYSIS OF DRIFT GILL NET FISHING BUSINESS IN SASAK VILLAGE SASAK RANAH PASISIE SUB-DISTRICT PASAMAN BARAT REGENCY WEST SUMATRA PROVINCE - Arni Wira Destika; Hendrik Hendrik; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                This study aims to analyze the amount of investment in drift gill net fishing business, analyze the income and profits of drift gill net fishing business, and analyze the feasibility of drift gill net fishing business. This research is conducted by using survey method and interview technique. The number of respondents in this study were 12. Based on the results of the research, the total investment for drift gill net fishing business with a fishing fleet measuring 5 GT IS IDR. 190.583.738 and gross income adalah IDR. 6.623.333 in one fishing trip, and the profit of drift gill net fishermen is IDR. 2.387.738 in one trip. Based on the calculation of the Revenue Cost of Ratio (RCR) investment criteria, a value of 1,59 means that RCR> 1 and the business of drift gill net fishing equipment are profitable and feasible to continue. While the Financial Rate of Return (FRR) of drift gill net fishing business is 90,6% and is greater than the current bank deposit interest rate, which is 6.5%, which means it is better to invest in the business at this time. The Payback Period of Capital (PPC) value is 70 which means that the investment in this business can be returned for 70 fishing trips                Keywords: Fisherman, fish gear, business feasibility analysis